Does Investment in Schooling Raise National Income? Evidence from Cross-Country Studies (2020)
The economics literature identifies three effects of schooling on national income; the direct effect on the earnings of the workers who receive the schooling and the external effects on workers’ earnings and on physical capital due to schooling’s spillover effect on the productivity of these other factors of production.  This paper reviews the estimates of the income elasticity of these three effects in the literature and finds that the evidence supports an elasticity of 0.34.  The associated marginal rates of return on national investment in schooling in 2000 are found to average about 12 percent in countries with high levels of schooling and about 25 percent in countries with low levels of schooling.